2007
DOI: 10.1007/s10433-007-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

The conceptualization and measurement of quality of life in older adults: a review of empirical studies published during 1994–2006

Abstract: The review included 47 papers. A total of 40 different measurements were applied in the studies, assessing most frequently functional status and symptoms. The most extensive psychometric evidence was documented for the SF-36. Although construct validity was reported in the majority of studies, minimal empirical evidence was given for other psychometric properties. Further, 87% of the studies lacked a conceptual framework and 55% did not report any methodological considerations related to older adults. Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 95 publications
(157 reference statements)
0
53
0
4
Order By: Relevance
“…Establishing an accepted definition of the concept has therefore posed challenges for researchers (Spirduso and Cronin 2001;Halvorsrud and Kalfoss 2007). However, while some suggest that through the development of population specific measures, the need for a concise QoL definition has been somewhat reduced (Ashley 2001), others propose the improvement of a common QoL assessment model (Halvorsrud and Kalfoss 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishing an accepted definition of the concept has therefore posed challenges for researchers (Spirduso and Cronin 2001;Halvorsrud and Kalfoss 2007). However, while some suggest that through the development of population specific measures, the need for a concise QoL definition has been somewhat reduced (Ashley 2001), others propose the improvement of a common QoL assessment model (Halvorsrud and Kalfoss 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Establishing an accepted definition of the concept has therefore posed challenges for researchers (Spirduso and Cronin 2001;Halvorsrud and Kalfoss 2007). However, while some suggest that through the development of population specific measures, the need for a concise QoL definition has been somewhat reduced (Ashley 2001), others propose the improvement of a common QoL assessment model (Halvorsrud and Kalfoss 2007). By 1997 Bowling (Bowling 1997) documented 73 measures of QoL, which may have been a somewhat conservative estimate given Huges and Hwang (as cited in [Halvorsrud and Kalfoss 2007)] suggestion that over a 1,000 items existed to measure the various aspects of QoL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a narrative review of 29 empirical studies on QoL among older adults from 2003-2013, findings showed that 90% of the studies lacked a theoretical or conceptual framework. [56] For those few studies in the review that implemented theoretical perspectives, it was difficult to discern how study variables were connected to the instruments. This difficulty may come from the lack of an existing universal theory of QoL.…”
Section: Lack Of Theoretical Perspectivementioning
confidence: 99%
“…Gleichzeitig ist nach wie vor eine willkürlich anmutende Verwendung des Begriffs "Lebensqualität" innerhalb und über verschiedene Disziplinen hinweg zu beobachten; Definition und Operationalisierung sind uneinheitlich [10]. Folglich fällt auch die Abgrenzung zu nahen Konstrukten wie "Wohlbefinden", "Glück" oder "subjektive Gesundheit" schwer [8,12,15]. Über die subjektiven Lebensqualitätstheorien alter Menschen in unterschiedlichen Lebensumständen ist wenig bekannt [2].…”
Section: Hintergrund Und Fragestellungunclassified